PENGARUH MOTIVASI EKSTERNAL DAN INTERNAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PDAM AMBON - Sapulette, Ludy (Arthavidya Jurnal Ilmiah Ekonomi, 2015)
This study aims to analyze the influence of internal and externalmotivation on employee productivity PDAM Ambon. Therefore, this study wasconducted in Ambon for two months.Primary data was collected throughquestionnaires distributed to 94 employees PDAM Ambon. Furthermore, thedata were analyzed using multiple regression analysis techniques.The resultsshowed a partial and simultaneously, the internal motivation (X1) and externalmotivation (X2) positive and significant impact on employee of PDAM Ambonproductivities. Thus the three hypotheses proposed in this study can beaccepted. These results indicate that to increase employee productivity,managers of PDAM Ambon need to motivate them to pay attention to bothinternal and external motivation factor.Keywords: internal motivation, external motivation, work productivity